Oenological Performances of New White Grape Varieties - Aécio Luís de Sousa Dias; Charlie Guittin-Leignadier; Amélie Roy; Somaya Sachot; Faïza Maçna; Damien Flores; Emmanuelle Meudec; Jean-Claude Boulet; Nicolas Sommerer; Aurélie Roland; Marie-Agnès Ducasse; Jean-Roch Mouret (Beverages, 2025)
The wine industry aims to reduce pesticide use by utilizing disease-resistant grape varieties, although their oenological potential remains underexplored. This study aimed to evaluate their oenological potential compared to traditional ones. Musts from resistant (Souvignier Gris, Sauvignac, Voltis, and Floreal) and traditional (Chardonnay, Sauvignon Blanc, and Viognier) varieties were fermented at laboratory scale with online CO2 monitoring, and two yeasts were used to study varietal responses to yeast impact. Wines were analyzed for metabolites from central carbon metabolism, aromas (varietal thiols, ethyl esters, acetate esters, and higher alcohols), and phenolic compounds (hydroxybenzoic acids, hydroxycinnamic acids, flavan-3-ols, and flavonols) using (U)HPLC methods. Principal component analysis (PCA) of all variables revealed Souvignier Gris grouped with a Sauvignon Blanc sample, partially due to varietal thiols. PCA of aromas (PC1: 37.7%, PC2: 17.8%) showed that Souvignier Gris and Sauvignac exhibited similar behavior to Sauvignon Blanc. The heat map of 19 phenolics showed Sauvignac and Sauvignon Blanc clustered, with lower phenolic abundance. This preliminary work contributes to a detailed characterization of the oenological potential of these new varieties and constitutes an essential step in identifying which traditional and well-known varieties they resemble. This will then enable the recommendation of cellar itineraries adapted to their profile.